Value Creation as a Productivity Instrument in Specialized Cooperatives with no Savings Section in Bogotá - Rodríguez Alvarado, Gloria Asceneth; Vásquez Bernal, Oscar Alejandro; Rodríguez Barrero, Mario Samuel (Cooperativismo & Desarrollo, 2022)
Summary This article aims to explain how 12 specialized cooperatives without savings section in Bogotá create value in terms of productivity under sustainability, through the analysis of indicators of continuity, social base, effectiveness, efficiency, solvency and indebtedness between 2015 and 2019. For this research, a database of the Superintendency of Solidarity Economy with financial information was used. The mixed approach allowed analyzing the results of the indicators and formulating a proposal aimed at creating value under the principles of cooperativism. As a result, it was observed that the cooperatives under study present consistency and robustness in their performance. Lastly, with this study it was concluded that favorable situations can be potentiated by analyzing their exercise reflected in the financial statements.